Polo‐like kinase 3 is associated with improved overall survival in cholangiocarcinoma. (10th April 2015) - Juntermanns, Benjamin; Sydor, Svenja; Kaiser, Gernot M.; Jaradat, Derar; Mertens, Joachim C.; Sotiropoulos, Georgios C.; Swoboda, Sandra; Neuhaus, Jan P.; Meng, Wei; Mathé, Zoltan; Baba, Hideo A.; Canbay, Ali; et al.
Abstract Background & Aims Cholangiocarcinomas (CCA) paradoxically express the death ligand TRAIL and thus, are dependent on effective survival signals to circumvent apoptosis. Hedgehog signalling exerts major survival signals in CCA by regulating serine/threonine kinase polo‐like kinase (PLK)2. We here aimed to examine the role of PLK1/2/3 expression for CCA tumour biology. Methods We employed CCA samples from 73 patients and human HUCCT–1/Mz–CHA1/KMCH‐1 CCA cells. Immunohistochemistry for PLK1/2/3 was performed using tissue microarrays from representative tumour areas. Results PLK1/2/3‐immunoreactive cancer cells were present in most of the CCA samples. However, only PLK1 and especially PLK3 were expressed in higher amounts within CCA cells as compared to normal liver. Given that fibroblast growth factor (FGF) can induce PLK3 expression and also is present in CCA, we examined the effect of FGF on PLK3 in vitro. Indeed, rhFGF rapidly increased PLK3 mRNA expression all three CCA cell lines giving an explanation for the abundant PLK3 presence in the tissue samples. Clinicopathologically, PLK3 expression was associated with decreased tumour cell migration and lymph/blood vessel infiltration whereas higher levels of PLK1 were correlated with larger tumour sizes. Moreover, strong PLK3 expression was associated with prolonged overall survival. Conclusions The results suggest that PLK3 predominantly is expressed in CCA cells and that high PLK3 expression correlates with prolonged overall survival. These observations might have implications for prognosis prediction of human CCA as well as the potential therapeutic use of polo‐like kinase inhibitors (i.e., PLK1/2 specifity).